Goal Orientations and their Relationship to Learning Strategies Of Mu’tah University Students - Al-Zghoul, Rafe (Jordan Journal of Educational Sciences, 2006)
This study aimed at investigating students’ achievement goal orientations, learning strategies, and the relationship between them. A random sample composed of 337 male and female students was chosen from the faculties of Arts, Science, and Educational Science at Mu’tah University. Members of the sample completed a questionnaire of achievement goals and The Approach to Studying Inventory(ASI). Results indicated that 89.6% of the students had a mastery orientation, 42.1% had a performance approach orientation, and 72.4% had a performance avoidance orientation. In addition, 74.2% of the students used a deep study strategy, 73.0% used a surface study strategy, and 52.5% used a strategic study strategy. Mastery goals proved to be positive predictors of deep and strategic study strategies; also, performance-avoidance goals are positive predictors of the surface study strategy, while performance-approach goals correlated significantly with the surface strategy, but did not contribute significantly to the variance of its score.